Changes [large type] - Lackey, Mercedes (Lackey, Mercedes. Collegium chronicles., 2012)
In the thrilling third volume of the epic Collegium Chronicles, orphaned Magpie pursues his quest for his parents' identity with burning urgency while being trained by the King's Own Herald as an undercover agent for Valdemar. Shy Bardic Trainee Lena has to face her famous but uncaring father, one of Valdemar's most renowned Bards. And Healing Trainee Bear must struggle against his disapproving parents, who are pressuring him to quit. Each of the three friends must face his or her demons and find their true strength. Bestseller